Influence of Substrate on Crystal Orientation of Large-Grained Si Thin Films Formed by Metal-Induced Crystallization - Kaoru Toko; Mitsuki Nakata; Atsushi Okada; Masato Sasase; Noritaka Usami; Takashi Suemasu (International Journal of Photoenergy)
Producing large-grained polycrystalline Si (poly-Si) film on glass substrates coated with conducting layers is essential for fabricating Si thin-film solar cells with high efficiency and low cost. We investigated how the choice of conducting underlayer affected the poly-Si layer formed on it by low-temperature (500°C) Al-induced crystallization (AIC). The crystal orientation of the resulting poly-Si layer strongly depended on the underlayer material: (100) was preferred for Al-doped-ZnO (AZO) and indium-tin-oxide (ITO); (111) was preferred for TiN. This result suggests Si heterogeneously nucleated on the underlayer. The average grain size of the poly-Si layer reached nearly 20 µm for the AZO and ITO samples and no less than 60 µm for the TiN sample. Thus, properly electing the underlayer material is essential in AIC and allows large-grained Si films to be formed at low temperatures with a set crystal orientation. These highly oriented Si layers with large grains appear promising for use as seed layers for Si light-absorption layers as well as for advanced functional materials.